Teacher Managerial Competence in Differentiated Learning - Endah Dwi Hayati; Sri Sulihingtyas Drihartati; Yosep Bambang Margono Slamet (LPPM Universitas 17 Agustus 1945 Semarang, 2026)
Teachers, as professionals, play a crucial role in managing learning in the classroom. One essential skill that teachers must have is managerial skills, which involve organizing learning activities, setting up the learning environment, and applying suitable methods for learning tasks. In the context of differentiated learning focused on student needs, teacher managerial competence is vital for designing and managing instruction tailored to each student's requirements. Differentiated learning is an approach that emphasizes meeting the needs, interests, and learning styles of individual students. This study was conducted using a literature review method, drawing data from various sources including books, articles, and relevant previous research. The review shows that for successful differentiated learning, teachers need to implement managerial strategies for identifying students’ learning needs, managing content, processes, learning products, and conducting regular formative assessments. Furthermore, teachers must create an environment that supports the learning process through strong collaboration among students, between teachers and students, and with parents. Therefore, improving teacher managerial skills is one way to achieve inclusive learning and accommodate student diversity.